Study on the aeroelastic performance of 15 MW wind turbine under yaw condition - Ma, Lu; Li, Yijia; Zhou, Le; Yang, Dinghua; Shen, Xin; Du, Zhaohui (Frontiers in Energy Research, 2025)
Introduction: The trend toward larger wind turbine has made the aeroelastic issues of the wind turbine blades more prominent. To investigate the effect of flexible deflection of hundred-meter-scale blades on wind turbine performance.Methods: The present study taking the IEA-15 MW wind turbine as the research object, and the aeroelastic coupling characteristics of the wind turbine under yaw condition are analyzed using the lifting-line free vortex wake model and a geometrically exact beam theory model.Results and Discussion: The results show that, the torsional deflection of the blades may cause the reduction of the angle of attack, leading to the decrease of the wind turbine loads. Furthermore, influenced by the additional velocity induced by blade flapwise deflection, the loads fluctuation of flexible blade is larger than those of rigid blade. As the yaw angle increases, the mean power of the wind turbine decreases, while the fluctuation amplitude increases. Besides, the mean value and fluctuation amplitude of the rotor tilt and yaw moments become larger, the angle of attack exhibits more significant fluctuation amplitude but reduced mean value, and the turbine wake contracts and skews more obviously.